Longs, shorts, and the cross-section of stock returns - Nezafat, Mahdi; Shen, Tao; Wang, Qinghai; Wu, Julie (Journal of Banking & Finance, 2022)
We study the relation between severe investor disagreement and stock returns based on the observed short-interest and long positions of hedge funds. We show strong disagreements are prevalent among active, sophisticated investors. From 1997 to 2014, 30% of highly shorted stocks have high hedge fund ownership, but these stocks do not earn abnormal returns. Evidence shows that large simultaneous holdings of short sellers and hedge fund managers likely arise from their information-acquisition activities. Although active long or short positions on average predict subsequent stock returns, neither long investors nor short sellers consistently prevail when the two sides disagree.